Web-based intervention for depressive symptoms in adults with types 1 and 2 diabetes mellitus: a health economic evaluation. (4th March 2018) - Nobis, Stephanie; Ebert, David Daniel; Lehr, Dirk; Smit, Filip; Buntrock, Claudia; Berking, Matthias; Baumeister, Harald; Snoek, Frank; Funk, Burkhardt; Riper, Heleen
Abstract : Background: Web-based interventions are effective in reducing depression. However, the evidence for the cost-effectiveness of these interventions is scarce. Aims: The aim is to assess the cost-effectiveness of a web-based intervention (GET.ON M.E.D.) for individuals with diabetes and comorbid depression compared with an active control group receiving web-based psychoeducation. Method: We conducted a cost-effectiveness analysis with treatment response as the outcome and a cost-utility analysis with quality-adjusted life-years (QALYs) alongside a randomised controlled trial with 260 participants. Results: At a willingness-to-pay ceiling of €5000 for a treatment response, the intervention has a 97% probability of being regarded as cost-effective compared with the active control group. If society is willing to pay €14 000 for an additional QALY, the intervention has a 51% probability of being cost-effective. Conclusions: This web-based intervention for individuals with diabetes and comorbid depression demonstrated a high probability of being cost-effective compared with an active control group. Declaration of interest: S.N., D.D.E., D.L., M.B. and B.F. are stakeholders of the Institute for Online Health Trainings, which aims to transfer scientific knowledge related to this research into routine healthcare.